The effects of budget deficit, investment and export on economic growth : evidence from developing countries [2008-2017] / Nurul Aiza Zainal Abidin - Zainal Abidin, Nurul Aiza
This study is to investigate the relationship between budget deficit, investment and export with economic growth in developing countries using panel data of 2008-2017.Other variables besides mentioned that incurred in this study is technology. Twenty-three country from developing country had chosen as sample and the data are collected from World Developing Indictor. Research from other study reveals that all of the variables might influence the economic growth. So, in this study, will determined which variables are most effected to the economic growth and looking for the relationship between each variable with the economic growth. The result showed the most significant variable effect to economic growth are budget deficit, investment and export. There are some method used in this study where to check the relationship of the variables with the economic growth. The method are panel regression test, panel correlation test, unit root test and granger causality test.